ANALYSIS OF NATIONALISM ATTITUDES BASED ON TEACHER MOTIVATION IN BORDER AREA - Sosiady, Mulia; Ermansyah, Ermansyah; Hamzaoui, Wafa; Landri, Pelican; Identiti, Identiti (Economic and Science Faculty of Islamic State University, 2025)
Rupat Utara and Rangsang Pesisir are areas located in the border zone between Indonesia and Malaysia. The significant potential for external influence in the border areas affects the level of nationalism among the people in the Rupat Utara and Rangsang Pesisir regions. As for the sample in this study involved 35 teachers from state high schools in Rangsang Pesisir and Rupat Utara, with a regression coefficient value for the educator motivation variable (X) of 0.899 and a t-value of 4.826. The positive value of the educator motivation coefficient indicates that educator motivation has a direct relationship with the increase in teachers' nationalist attitudes. This shows that as educator motivation increases, so does the improvement in teachers' nationalist attitudes at public high schools in Rupat Utara and Rangsang Pesisir. The influence of educator motivation on the improvement of teachers' nationalist attitudes in state high schools in Rupat Utara District and Rangsang Pesisir District can contribute an impact of 41.4%, meaning that educator motivation can explain 41.4%. Meanwhile, the remaining 58.6% is influenced or explained by other variables not included in this research model.